Long‐term outcomes after NORSE: Treatment with vagus nerve stimulation. Issue 4 (9th October 2022) - Espino, Poul H.; Burneo, Jorge G.; Moscol, Gaby; Gofton, Teneille; MacDougall, Keith; Suller Marti, Ana
Abstract: New‐onset refractory status epilepticus (NORSE) is associated with high mortality, therapy‐resistant epilepsy (TRE), and poor cognitive and functional outcomes. Some patients develop multifocal TRE, for whom surgery with a curative intention, is not an option. In these patients, vagus nerve stimulation (VNS) is performed as a palliative treatment. We report the long‐term outcomes regarding seizure frequency, functional and cognitive outcome, and effectiveness of VNS in two patients with TRE as a consequence of NORSE. In the first patient with cryptogenic NORSE, VNS implantation occurred during the acute stage, probably contributing to the cessation of her status epilepticus. However, in the long‐term follow‐up, the patient persisted with daily multifocal seizures. In the second patient, VNS implantation was delayed to manage his epilepsy when the NORSE, ultimately due to autoimmune encephalitis, had resolved. During long‐term follow‐up, no reduction in seizure frequency was achieved. This evidence supporting the use of VNS in patients with TRE after NORSE warrants further investigation.